2014
DOI: 10.1111/zph.12171
|View full text |Cite
|
Sign up to set email alerts
|

Human–Dromedary Camel Interactions and the Risk of Acquiring Zoonotic Middle East Respiratory Syndrome Coronavirus Infection

Abstract: Impact• Dromedary camels are the only animal species for which there is convincing evidence that it is a host species for MERS-CoV and hence a potential source of human infections.• Direct contact with dromedary camels can only explain a small proportion of the primary cases. Other possible sources and vehicles of infection include food-borne transmission through consumption of unpasteurized camel milk and raw meat, medicinal use of camel urine and zoonotic transmission from other species.• In the Arabian Peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
145
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 29 publications
1
145
0
Order By: Relevance
“…10,29,43 Although the exact mode of transmission between camels and humans is unknown, it is speculated that transmission may occur through direct contact, ingestion of unpasteurized camel milk, or contact with respiratory droplets or nasal secretions, which have been shown to carry high viral loads. 1,9,27,44 Despite the high prevalence of MERS-CoV in camels, viral transmission from camels to humans appears to be limited, and multiple countries with seropositive camels have yet to detect MERSCoV infections in humans. 18,32,49 …”
Section: Human Mers-cov Infectionsmentioning
confidence: 99%
“…10,29,43 Although the exact mode of transmission between camels and humans is unknown, it is speculated that transmission may occur through direct contact, ingestion of unpasteurized camel milk, or contact with respiratory droplets or nasal secretions, which have been shown to carry high viral loads. 1,9,27,44 Despite the high prevalence of MERS-CoV in camels, viral transmission from camels to humans appears to be limited, and multiple countries with seropositive camels have yet to detect MERSCoV infections in humans. 18,32,49 …”
Section: Human Mers-cov Infectionsmentioning
confidence: 99%
“…Thus, this might have paved the way for possible spillover events between camels and human being; which manifested as a zoonosis like MERS. 27 A review of the South Korean outbreak in 2015, by Majumder et al revealed findings similar to those generated in KSA, but the case-fatality rate as discussed earlier was nearly half that of the Saudi's. 28 Nevertheless, it is important to mention here the concept of -super spreaders‖, where the literature has established the 20/80 rule in which a small percentage of individuals in any community is noted to direct most transmission occurrences.…”
Section: The Hostmentioning
confidence: 72%
“…Furthermore, there is evidence regarding other causes of infection, such as consuming camel raw meat and unpasteurized milk, remedial utilization of camel urine, and zoonosis from other species. 24 Regarding the human host, an epidemiological study conducted by Alsahafi et al that included the total reported cases of MERS-CoV in KSA between 2012 and 2015, has revealed that two-thirds of patients were males and that one third of them were elderly (>60 years old). Interestingly, the gender difference was reversed when considering the healthcare workers, where about 60% of the affected were females.…”
Section: The Hostmentioning
confidence: 99%
“…The majority of primary cases do not report contact with animals 76,77 . Dromedary camels are ubiquitously present in the Middle East and have been part of desert cultures for centuries with cultural and economic importance.…”
Section: Mers-cov Infection In Animals Appearsmentioning
confidence: 99%